2017
DOI: 10.1515/jbcpp-2016-0096
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum gratissimum Linn. Leaf extract inhibits free radical generation and suppressed inflammation in carrageenan-induced inflammation models in rats

Abstract: Background: Ocimum gratissimum leaf is used in managing rheumatism and other inflammatory conditions. In this study, we investigated the antioxidant and anti-inflammatory effects of phenolic extract obtained by sequential methanol extraction of O. gratissimum leaves (MEOg). Methods: The methanol extract (MEOg) was obtained after sequential maceration (n-hexane, chloroform and methanol) of dried O. gratissimum leaves. The fingerprint of the extract was obtained using a high-performance liquid chromatrographic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…Applied externally, the leaves are used to treat rheumatism and lumbago (Bown, 1995). Moreover, pharmacological studies have shown that the extract and essential oil from the leaves O. gratissimum significantly reduce carrageenan-induced rat paw edema and suppress collagen-induced arthritis in rats (Ajayi et al, 2017;Madhu and Harindran, 2014;Paula-Freire et al, 2013). The traditional claims founded on ethnopharmacological information as well as in vitro and in vivo pharmacological reports of the antiinflammatory properties of O. gratissimum are undoubtedly due to numerous bioactive constituents found in the plants acting synergistically or each having its respective pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Applied externally, the leaves are used to treat rheumatism and lumbago (Bown, 1995). Moreover, pharmacological studies have shown that the extract and essential oil from the leaves O. gratissimum significantly reduce carrageenan-induced rat paw edema and suppress collagen-induced arthritis in rats (Ajayi et al, 2017;Madhu and Harindran, 2014;Paula-Freire et al, 2013). The traditional claims founded on ethnopharmacological information as well as in vitro and in vivo pharmacological reports of the antiinflammatory properties of O. gratissimum are undoubtedly due to numerous bioactive constituents found in the plants acting synergistically or each having its respective pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Preparations were examined under a microscope with 40× magnification. The number of leukocytes was calculated by the following formula [19]:…”
Section: Leucocyte Countmentioning
confidence: 99%
“…The exudate was centrifuged at 5400 g for 10 min at 4 • C to obtained supernatant aliquoted and then stored at −8 • C [19]. TNF-α was determined using an ELISA kit (Sigma, St. Louis, MO, USA), according to the manufacturer's instructions.…”
Section: Leucocyte Countmentioning
confidence: 99%
“…Inflammatory processes are suppressed with anti-inflammatory drug in medical practice. Ethnomedical preparations improves clinical disease conditions by suppression of inflammatory processes (4)(5)(6). Helianthus annuus Linn.…”
Section: Introductionmentioning
confidence: 99%